The Structure of Postal Routes of the Grand Duchy of Lithuania in the 16th–18th Centuries∗ - Čelkis, Tomas (Lietuvos istorijos studijos, 2022)
This paper analyzes the dynamics of the postal route system of the Grand Duchy of Lithuania in the 16th–18th centuries. The first postal route connected Vilnius and Krakow in 1562 – weekly postal services were rendered. In 1669, postal carriages started running from Moscow to Vilnius and then further on through Tilsit to Königsberg. The GDL postal route network underwent its largest expansion in the 18th century. An important postal line proceeded along the route of Warsaw – Grodno – Kaunas – Jelgava – Riga. Part of it coincided with the Warsaw – Vilnius route; at Ratnyčia, the postal carriage would turn northeast and continue via Merkinė and Varėna to Vilnius. From Vilnius, one postal route led to Königsberg via Kaunas, and another to Moscow; there are also data about a postal line to Polotsk. Another crossroads of the GDL’s postal routes was Grodno. The routes leading from Warsaw to Kaunas, Vilnius, and Riga intersected there. Separate lines to Lublin and Slonim were in operation; one of the postal routes led to the border of the Russian Empire. The network of the GDL’s postal routes also consisted of other roads. The location of some of them were subject to change due to the political situation, natural disasters, and seasonal practicability.